2005
DOI: 10.1177/026142940501900311
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Master Music Teachers and Master Students: Counseling Concerns

Abstract: the relationship between master 1nusic teachers and 1naster students: counseling concerns AbstractThe relationship between the music instructor and the pupil has only been superficially examined. As advanced students in music become even more talented and sophisticated, they need increasingly greater amounts of individual attention from accomplished musicians and instructors. As students hone and sharpen their skills, they need increasing amounts of attention, supervision and nurturing from their master teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In music education, seemingly, the problem arises, not when controlled regulations are present [23], but when psychological needs are unfulfilled, since this shortfall has been linked with dropout [20]. However, conservatoire teachers tend to be not only demanding of externallyreferenced performance standards, but also controlling [32] and prescriptive of the ways to accomplish them; thus, leaving students with limited opportunity to feel that they can influence the ways in which they are taught [33]. Contrastingly, it is PNS (including autonomy need satisfaction) and autonomous motivation which have been related with lower negative and higher positive emotions, with higher preference for challenges, with higher frequency of both practice and practice of high quality [34], and lastly with intentions to continue practising; hence, PNS should be taken into consideration when facing problems of retention and dropout [1].…”
Section: Psychological Needs Satisfaction and Behavioural Regulationsmentioning
confidence: 99%
“…In music education, seemingly, the problem arises, not when controlled regulations are present [23], but when psychological needs are unfulfilled, since this shortfall has been linked with dropout [20]. However, conservatoire teachers tend to be not only demanding of externallyreferenced performance standards, but also controlling [32] and prescriptive of the ways to accomplish them; thus, leaving students with limited opportunity to feel that they can influence the ways in which they are taught [33]. Contrastingly, it is PNS (including autonomy need satisfaction) and autonomous motivation which have been related with lower negative and higher positive emotions, with higher preference for challenges, with higher frequency of both practice and practice of high quality [34], and lastly with intentions to continue practising; hence, PNS should be taken into consideration when facing problems of retention and dropout [1].…”
Section: Psychological Needs Satisfaction and Behavioural Regulationsmentioning
confidence: 99%
“…While other domains of teaching (e.g., school) have changed considerable over the last century or so, the teaching style in studio classical music training is steeped in a master-apprentice model, in which the teacher is the active and prescriptive expert, and the student is passive (Gaunt, 2008;McPherson & Gabrielsson, 2002). Recent research has concluded that advanced classical music MOTIVATION AND COPING WITH ASSESSMENT 30 training might still be rather controlling (Evans, 2015;Syrjala, Saarela, & Lehtonen, 2005). The musicians investigated in Study might have been affected by this overall culture of control.…”
Section: On the Relationships Between Motivation Stress And Coping Wmentioning
confidence: 99%
“…(2) Autonomy support is context-specific and some behaviors that may be perceived as controlling in other contexts (e.g., being told what to do; Reeve et al, 1999) are not perceived as such in music. A plethora of researchers from independent groups in at least three countries concluded the general lack of autonomy in higher music education (Evans, 2015; McPherson & Gabrielsson, 2002; Syrjala et al, 2005), which renders the first hypothesis unlikely, though it is possible that higher music education provides more autonomy to students than lower-level conservatoire-like settings. Therefore, it could be that autonomy support is seen differently in music at different levels of education, and further research needs to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the classical performance training has a long history of cultivating conformity and adherence to strict rules and offers historical evidence for a culture of controlling teaching styles in music (McPherson & Gabrielsson, 2002). Recent research concluded that advanced classical music training might still be rather controlling (Evans & Bonneville-Roussy, 2016; Syrjala et al, 2005), and higher instrumental music education as a result of this teaching tradition may be an unpredictable and ineffective atmosphere in promoting students’ motivation and independence (Gaunt, 2008, 2010). To further understand the issue, in this research, we looked at how the supportive and controlling teaching styles of music teachers in one-to-one settings can influence their students’ well-being by illuminating teachers’ and students’ perceptions of teaching in higher music education institutions in the United Kingdom.…”
mentioning
confidence: 99%